TEACHER PERCEPTIONS OF THE USE OF ARTIFICIAL INTELLIGENCE (AI) IN SCIENCE LEARNING IN MAKASSAR CITY - Rizki Trisnawaty Arwien; Zose Wirawan; Tismi Dipalaya; Nurul Mutmainnah (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
This study aims to analyze teachers' perceptions of the use of Artificial Intelligence (AI) in science learning (Ilmu Pengetahuan Alam/IPA) in Makassar City. The method used is descriptive quantitative, with data collected through a Likert-scale questionnaire distributed to 25 junior high school science teachers. The questionnaire was developed based on five main aspects: teaching experience, interest and motivation, benefits and impacts, challenges and obstacles, and expectations regarding the use of AI. The results of the study indicate that the majority of teachers have a positive perception of the integration of AI in science education. Teachers reported benefits in terms of increased student motivation, more innovative learning experiences, and easier explanations of abstract scientific concepts. However, several challenges remain, such as limited access to devices, internet connectivity, and technical skills. Despite these challenges, teachers demonstrate a high level of readiness and enthusiasm to participate in further training and express strong expectations for AI to be formally integrated into the science curriculum. The study recommends policy support, ongoing professional development, and infrastructure improvements to ensure the effective and equitable implementation of AI across schools